Advanced radar techniques and systems - Galati, Gaspare (Institution of Engineering and Technology, 1993)
Within the wide and fascinating field of radar techniques and systems, this book describes in detail a number of areas of research related to system architecture and design, phenomenology, array antennas and signal processing. The topics covered include: radar detection; phenomenology of clutter and related constant false alarm rate (CFAR) processors; Doppler techniques for surveillance radar, multifunction radar and synthetic aperture radar; clutter suppression: moving target indicators and detectors, adaptive and optimum MTI (moving target indication); rejection of jamming in space and frequency domains; concepts of radar target identification; architectural options and trend in radar signal processing; phased arrays (array theory, analysis and synthesis techniques; array elements and mutual coupling effects; architecture, elements, design criteria and low-sidelobe techniques for active arrays); bistatic radar; and space-based radar.